Impact Of Foreign Direct Investment In Indian Economy (International Journal of Food and Nutritional Sciences, 2022)
The aim of this paper is that examine the impact of foreign direct investment in Indian economy. It has established the fact that foreign direct investments has long term impact on Indian economy and FDI is the most important key to economic development of India. The paper has presented data from 2000-01 to 2019-20 to evaluate the pattern and trends of FDI on Indian economy.